Dnd1 Knockout in Sturgeons By CRISPR/Cas9 Generates Germ Cell Free Host for Surrogate Production - Baloch, Abdul Rasheed; Franěk, Roman; Tichopád, Tomáš; Fučíková, Michaela; Rodina, Marek; Pšenička, Martin (Animals, 2019)
Sturgeons also known as living fossils are facing threats to their survival due to overfishing and interference in natural habitats. Sterlet (Acipenser ruthenus) due to its rapid reproductive cycle and small body size can be used as a sterile host for surrogate production for late maturing and large sturgeon species. Dead end protein (dnd1) is essential for migration of Primordial Germ Cells (PGCs), the origin of all germ cells in developing embryos. Knockout or knockdown of dnd1 can be done in order to mismigrate PGCs. Previously we have used MO and UV for the aforementioned purpose, and in our present study we have used CRISPR/Cas9 technology to knockout dnd1. No or a smaller number of PGCs were detected in crispants, and we also observed malformations in some CRISPR/Cas9 injected embryos. Furthermore, we compared three established methods to achieve sterility in sterlet, and we found higher embryo survival and hatching rates in CRISPR/Cas9, UV and MO, respectively.
Keywords: PGCs; caviar; Acipenser; genome editing; conservation; morpholino oligonucleotide